New answers to old questions: The effects of the minimum wage hike in Spain in 2019 - Michael Christl; Andrea Cubells Enguídanos; Filippo di Pietro (Global Labor Organization (GLO), 2024)
Our paper examines the effects of the significant 2019 minimum wage hike in Spain on labour market outcomes, prices, and firm bankruptcies. We use the synthetic control method (SCM) to analyze the impact of the policy on the Spanish economy. We find no significant impact of the minimum wage increase on labour market outcomes for low-skilled individuals, suggesting no major job losses or increased unemployment among this group. However, we observe a significant increase in prices, especially for services and processed food, with treatment effects reaching up to 3 percentage points in 2021 relative to the synthetic control group. In addition, we observe a slight increase in firm bankruptcies in industry and construction during the COVID-19 pandemic. While our results suggest that the minimum wage increase did not lead to significant job losses among vulnerable groups, it did lead to higher prices in certain sectors, which could negatively affect consumers. This is consistent with recent research from Germany, which found minimal effects on labour market outcomes but significant effects on prices following the introduction of a minimum wage.
Keywords: J20; J38; J48; 330; Minimum wage; Synthetic Control Method; labour market; prices; employment